Dr. Scott Spiro — Deep Plane Facelift — West Orange - Spiro, Scott (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Scott Spiro, practicing in West Orange, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003383; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; west orange